Perverzija i metoda : Žižekova ‘platonska ljubav’ za film, dijalektika egzemplifikacije i katastrofa psihoanalize u kinematičkom diskursu filozofije - Mikulić, Borislav (Array, 2013)
The article discusses the relation between the paradigmatic status of film and use of film analogies in the psychoanalytic discourse on society and culture by Slavoj Žižek, which represents the very ground of his philosophical discourse in general. In the first part, starting with a recent discussion by different English and American scholars on controversial aspects of Slavoj Žižek’s activity in academia and on a broader public scene, the paper discusses on some parallel examples and inherent motivators of the form-content controversy in philosophy and pop-culture as well as Žižek’s interpretation of his position. In the second part, the article discusses Žižek’s sporadic meta-reflection on exemplification and provides arguments for the thesis that, in Žižek, on the ground of his ontology of the virtual, one encounters a double conception of ‘inherence’ (paradigmatic and analogical) between instance and principle, its consequence is a shift in the use of film examples from analogy of objects to analogy of analyses, which makes up a typical conflict between the metonymic and metaphorical evasion of discourse. On this background, the article reexamins the general contention against Žižek of a ‘virtual totalitarianism’ without contingency of meaning and sense, and points to the position of the subject without discourse as another ground for condition analysis of truth. In the third part, the paper analyses and evaluates Žižek’s own understanding of his cinematographic illustrations and his peculiar, performing and self-referrential, method of resolving the epistemological problem of film interpretation through imaginary identification or ‘empathy’ with film objects. In the fourth part, the paper discusses the apparent asymmetry between Žižek’s application of psychoanalytic doctrines onto film criticism, on one side, and, on the other, his hardly elaborated apotheosis of the so-called ‘cinematic materialism’. It is argued that this asymmetry causes in the result what Žižek rejects in principle: a substitution of materialism and contingency of truth-search for a holism of sense. This seems, in consequence, to corroborate the psychoanalytic discourse on cinematography beeing the very ground of Žižek’s analytic discourse in general.